The Role of Blockchain Technology in Food Security Assurance in the European Union - Lubis, Mitra Musika; Chai, Napat; Al-Taani, Fadi (Techno Agriculturae Studium of Research, 2025)
This research was conducted to explore the role of blockchain technology in ensuring food safety in the European Union. Blockchain has been identified as a technology that can improve transparency and traceability in the food supply chain. The study aims to assess the level of blockchain adoption in the EU food sector, identify the challenges that hinder the adoption of this technology, as well as analyze its impact on food security. This research method uses a descriptive-qualitative approach, which involves literature analysis, industry reports, and interviews with experts. The results show that blockchain adoption is still low, especially among regulators and retailers, with the main obstacles being unsupportive regulation and uneven technological infrastructure. The conclusion of this study emphasizes the importance of developing more supportive policies as well as improving infrastructure to facilitate wider and more equitable adoption of blockchain in the food supply chain in the European Union.